Numerical measures of the degree of non-proportionality of multiaxial fatigue loadings - A. Bolchoun; H. Kaufmann; C. M. Sonsino (Fracture and Structural Integrity)
The influence of the non-proportional loadings on the fatigue life depends on the material ductility. Ductile materials react with a shortening of lifetime compared to proportional loading conditions. For a semiductile material there is almost no difference between proportional and non-proportional loadings with respect to the fatigue life. Brittle materials show an increase of the lifetime under non-proportional loadings. If fatigue life assessment is performed using stress-based hypotheses, it is a rather difficult task to take into account material ductility correctly, especially the fatigue life reduction as displayed by ductile materials. Most stress-based hypotheses will compute a longer fatigue life under non-proportional loading conditions. There are also hypotheses, which already include quantitative evaluation of the non-proportionality (e.g. EESH, SSCH and MWCM). Anyway in order to improve assessment for ductile materials, some sort of numerical measure for the degree of non-proportionality of the fatigue loading is required. A number of measures of this kind (or non-proportionality factors) were proposed in the literature and are discussed here: - the factor used in EESH is a quotient of stress amplitudes integrals, - the factor according to Gaier, which works with a discrete stress tensor values in a scaled stress space, - the factor according to Kanazawa, which makes use of plane-based stress values, - the factor used in MWCM, which exploits stress values in the plane with the highest shear stress amplitude, a new non-proportionality factor, which is based on the correlation between individual stress tensor components, is proposed. General requirements imposed on the non-proportionality factors are discussed and each of the factors is evaluated with respect to these requirements. Also application with the stress-based hypotheses is discussed and illustrated using the experimental data for aluminum and magnesium welded joints under constant and variable amplitude loadings.